Entre disputas partidistas y supervivencia. La guerra de los Mil Días (Colombia 1899-1902) - Escobar Guzmán, Brenda (Anuario de Historia de América Latina, 2021)
This article argues that the ideological conflicts that set Colombian notables against each other in the 19th century can explain the discursive construction of the belligerent scene that started wars, but they do not fully explain their development. First, an overview of the 19th century political conflicts in Colombia is offered, summarizing the discussions they were based on. Subsequently, the text focuses on the last of those internal wars, the "Thousand Days’ War”. It aims to show that although several of the debates of transcendent order that had appeared in previous conflicts are also observed in this one, during the war these great causes lost strength and actions for mere survival generated in the heat of the armed confrontation played a more important role to define friends and enemies.
Keywords: Colombian History; 19th Century Politics; Political Parties; Civil War; Thousand Day's War